The importance of teacher participation in student reflexive construction (Research, Society and Development, 2019)
A parameter is made about the ideological influence and the importance of fostering students' critical sense through the perspective of the movie The Wave (2008) and the novel All Quiet on the Western Front (1929). The promotion of teaching and the improvement of education should be focused on the importance of developing students' reflection, turning them into citizens and not merely bureaucratized labor. Therefore, the objective is to expose the importance of the participation of educators in the development of critical and reflective sense of the students. Thus, this work has as methodology, bibliographical research and document analysis.